NILAI MORAL TOKOH UTAMA DALAM NOVEL PADA SEBUAH KAPAL KARYA NH. DINI - Widola, Tri; Bahardur, Iswadi; Zulfitriyani, Zulfitriyani (Pendidikan Bahasa Indonesia, 2014)
This study aims to describe the main character of moral values associated with a conscience, freedom and responsibility, rights and obligations, as well as the values and norms in the novel Pada Sebuah Kapal by Nh. Dini. This research is a qualitative study using descriptive methods . Object of this research is the novel Pada Sebuah Kapal by Nh. Dini. The data in this study in the form of words, sentences and dialogue related to the moral character of Sri and Michael. Sources of data in this study is novel Pada Sebuah Kapal by Nh. Dini. The results of this study demonstrate the value of the moral protagonist can be seen from the actions and behavior of characters in the form of speech, and events that made the main character played by individual leaders in Sri novel Pada Sebuah Kapal by Nh. Dini related to : (1) conscience, (2 ) freedom and responsibility, (3) the rights and obligations, (4) values and norms.Â